Penetration monitoring of drugs and additives by ATR-FTIR spectroscopy/tape stripping and confocal Raman spectroscopy – A comparative study - Binder, Lisa; Kulovits, Eva Maria; Petz, Romana; Ruthofer, Johanna; Baurecht, Dieter; Klang, Victoria; Valenta, Claudia (European journal of pharmaceutics and biopharmaceutics, 2018)
[Display omitted] Vibrational spectroscopy is a useful tool for analysis of skin properties and to confirm the penetration of drugs and other formulation compounds into the skin. In particular, attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy and confocal Raman spectroscopy (CRS) have been optimised for skin analysis. Despite an impressive amount of data on these techniques, a comparative methodological assessment for skin penetration monitoring of model substances is still amiss. Thus, in vitro skin penetration studies were conducted in parallel using the same porcine material and four model substances, namely sodium laureth sulfate (SLES), sodium dodecyl sulfate (SDS), sulfathiazole sodium (STZ) and dimethyl sulfoxide (DMSO). ATR-FTIR spectroscopy in combination with tape stripping and CRS were employed to evaluate the skin penetration of the applied substances. In addition, the skin hydration status or change in skin hydration after application was investigated. The results show that both methods provide valuable information on the skin penetration potential of applied substances. The penetration profiles determined by CRS or ATR-FTIR/tape stripping were comparable for all substances; a slow decrease in relative substance concentration was visible from the skin surface inwards within the stratum corneum (SC). In general, deeper penetration into the SC was observed with CRS, which may be related to the depth resolution of the employed device. However, when related to the respective total SC thickness of each experiment, the penetration depths determined by parallel CRS and ATR-FTIR analysis were in good agreement for all model substances. The observed order of the penetration depth was DMSO > SDS > SLES > STZ with both techniques. A decrease of the relative concentration to 10% of the maximum value was found approximately between 34 and 89% of total SC thickness. Summarising these findings, advantages and drawbacks of the two techniques for in vitro skin penetration studies are discussed.